2020
DOI: 10.3389/fimmu.2020.00064
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activation and Organ Damage After Trauma—Differential Immune Response Based on Surgical Treatment Strategy

Abstract: Background: The complement system is part of the innate immunity, is activated immediately after trauma and is associated with adult respiratory distress syndrome, acute lung injury, multiple organ failure, and with death of multiply injured patients. The aim of the study was to investigate the complement activation in multiply injured pigs as well as its effects on the heart in vivo and in vitro. Moreover, the impact of reamed vs. non-reamed intramedullary nailing was examined with regard to the complement ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 74 publications
0
25
0
Order By: Relevance
“…Complement hemolytic activity via the classical pathway was performed as described previously 23 . This method allows us to determine the hemolytic ability of porcine serum by complement activation.…”
Section: Methodsmentioning
confidence: 99%
“…Complement hemolytic activity via the classical pathway was performed as described previously 23 . This method allows us to determine the hemolytic ability of porcine serum by complement activation.…”
Section: Methodsmentioning
confidence: 99%
“…High plasma levels of HMGB1 are associated with increased complement activity as indicated by elevated soluble C5b-9 plasma levels that are generated during the late phase of complement activation [6]. The connection between complement activation and cardiac depression is well described after trauma [33] and sepsis [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…These results clearly underline the importance of a second hit phenomenon, which may not be clinically apparent during surgery. [ 9 , 10 ] They also reinforce the importance of patient assessment to achieve the goal of safe definitive surgery. [ 11 ] A recent comparison of existing scores revealed that patient assessment is safer when multiple parameters are used, especially when they cover several pathogenetic cycles.…”
Section: Polytrauma Management—an Update On New Aspectsmentioning
confidence: 91%